2014
DOI: 10.1002/j.0022-0337.2014.78.4.tb05713.x
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Dental Students’ and Faculty Members’ Attitudes About Technology, Instructional Strategies, Student Diversity, and School Duration: A Comparative Study

Abstract: In this study, attitudes and perceptions of U.S. dental students and faculty members were evaluated regarding four aspects of dental education: technology integration, instructional strategies, student diversity, and school duration. A survey instrument with eight statements using a ive-point Likert scale and a free-text comment section was developed and distributed through SurveyMonkey. A total of 426 students and 187 faculty members from ten U.S. dental schools participated, a response rate of 17 percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
1
12
0
3
Order By: Relevance
“…In the statement about program duration, most participants disagreed or strongly disagreed that it should be increased. This data is consistent with that found by Abdelkarim et al (14). A large portion of the participants agreed there is a need for specialist education, a result similar to that found by Walton et al (18), who examined Canadian dental students.…”
Section: Discussionsupporting
confidence: 91%
“…In the statement about program duration, most participants disagreed or strongly disagreed that it should be increased. This data is consistent with that found by Abdelkarim et al (14). A large portion of the participants agreed there is a need for specialist education, a result similar to that found by Walton et al (18), who examined Canadian dental students.…”
Section: Discussionsupporting
confidence: 91%
“…14,[27][28][29] Although, some hesitations of faculty to change their teaching styles to incorporate e-learning have been associated with low perceived benefit, time intensiveness, and perceived difficulty of developing these tools. [30][31][32] Future research should explore how to reconcile the disconnect between student and faculty preference for use of YouTube as learning tool for clinical dental procedures. It is important for dental educators to adapt one author's opinion that "the ultimate goal is to bridge the generations that are part of the educational process and support the mission of dental schools to educate competent oral healthcare professionals."…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 survey of 24 dental schools in the U.S., Canada, and Puerto Rico found that 59% of the students preferred printed books and 50% said they did not use the VitalBook in schools where the digital library had been adopted 10 . A more recent survey gauged the opinion of 187 faculty members and 426 students at ten U.S. dental schools 11 . In that study, 45% of students agreed or strongly agreed with a choice of electronic textbooks over printed books, while 34% preferred printed books to electronic ones and 22% were undecided.…”
mentioning
confidence: 99%